Answer:
x=-0.4
Step-by-step explanation:
We have the equation:
[tex]-9x+0.4=4[/tex]
First, the operation to move all the constants to the right side is subtraction since we would have to subtract 0.4 from each side, let's see this:
[tex]-9x+0.4=4\\-9x+0.4-0.4=4-0.4\\-9x=3.6[/tex]
Now, we have all the constants on the right side of the equation.
Now, the operation we need to perform to isolate the variable is division (since the x has a -9 that is being multiplied by x) we need to do the opposite operation:
[tex]-9x=3.6\\\frac{-9x}{-9} =\frac{3.6}{-9} \\x=-0.4[/tex]
Thus, the answer to this equation is x= -0.4
Answer:
a)
Subtract 0.4 from both side.
-9x +0.4 = 4
-9x + 0.4 - 0.4 = 4 - 0.4
-9x = 3.6
b)
divide by -9 both side
-9x/-9 = 3.6/-9
x = -0.4
Step-by-step explanation:
-9x+0.4=4
-0.4 -0.4
_______________
-9x=3.6
__ __
-9 -9
________________
x=-0.4
AM really good !
Step-by-step explanation:
Aspirin A bottle contains a label stating that it contains Spring Valley pills with 500 mg of vitamin C, and another bottle contains a label stating that it contains Bayer pills with 325 mg of aspirin. When testing claims about the mean contents of the pills, which would have more serious implications: rejection of the Spring Valley vitamin C claim or rejection of the Bayer aspirin claim? Is it wise to use the same significance level for hypothesis tests about the mean amount of vitamin C and the mean amount of aspirin? Rejection of the claim about______is more serious because the wrong______V dosage could cause more serious adverse reactions than a wrong______dosage. It would be wise to use a_______significance level for testing the claim about the aspirin.
Answer:
Rejection of the claim about aspirin is more serious because the wrong aspirin dosage could cause more serious adverse reactions than a wrong vitamin C dosage. It would be wise to use a greater significance level for testing the claim about the aspirin.
Step-by-step explanation:
The wrong dosage of aspirin will cause more damage than a wrong dosage of vitamin C. Then, if we perform an hypothesis test for each mean, the rejection of the claim about the aspirin content is more serious than the vitamin C content.
In the case of the aspirin, we want to minimize the Type II error (accepting a false null hypothesis). This can be achieved increasing the sample size or/and increasing the significance level. Then, a significative difference between the claimed content and the sample content will be easily detected.
WILL MARK BRAINLIEST
Sherlene bought 3 pounds of coffee and 2 pounds of chocolate for a total of $24. Which equation, written in standard form, correctly represents this scenario and correctly indicates what the
variables represent?
A) The correct equation is 3x + 2y = 24, where x is the price per pound of coffee and y is
the price per pound of chocolate.
B) The correct equation is 5x + y = 24, where x is the combined price per pound of
coffee and chocolate, and y is the total number of pounds purchased.
C) The correct equation is 3x + 2x + y = 24, where x is the combined price per pound of
coffee and chocolate, and y is the total number of pounds purchased.
D) The correct equation is 3x + 2y = 24, where x is the price per pound of chocolate and
y is the price per pound of coffee.
Answer:
AAAAAAAAAAAA answer is A
Step-by-step explanation:
POSSIBLE POINTS: 1
In the US, the average citizen receives an annual dose of 360 mrem of radiation. If eating a banana creates a 0.01 mrem dose, how many bananas
are equivalent to the annual dose of an average citizen?
720 bananas
36.000 bananas
25,000 bananas
180,000 bananas
Answer:
36,000
Step-by-step explanation:
So all we have to do is divide 360 by 0.01. that equals 36,000
Solve the equation sin sq x = 3cos sq x.
The value of x that satisfies the equation if x lies in the second quadrant is °.
The value of x that satisfies the equation if x lies in the third quadrant is
Answer:
Second quadrant = 120°.
Third quadrant = 210°
Step-by-step explanation:
We are given that:
[tex]sin^2(x) = 3cos^2(x)[/tex]
The following property is known:
[tex]sin^2(x) +cos^2(x)=1\\[/tex]
Combining both expressions:
[tex]sin^2(x) =1-cos^2(x)\\sin^2(x) = 3cos^2(x)\\\\1-cos^2(x) = 3cos^2(x)\\cos^2(x)=\frac{1}{4}\\cos(x)=\pm \frac{1}{2}[/tex]
If x lies in the second quadrant, then cos(x) = -1/2:
[tex]x=cos^{-1}(1/2)\\x=120^o[/tex]
The value of x that satisfies the equation if x lies in the second quadrant is 120°.
If x lies in the third quadrant, then cos(x) = -1/2:
[tex]x=120+90=210^o[/tex]
The value of x that satisfies the equation if x lies in the third quadrant is 210°
Answer:
The value of x that satisfies the equation if x lies in the second quadrant is 120
The value of x that satisfies the equation if x lies in the third quadrant is
240
Step-by-step explanation:
This is correct for Plato/Edmentum users :) Hope I could help !
Someone let me know this answer
Ellie goes out to dinner with her family. The total bill is $57. They decide to leave a 20% tip. How much money should they leave as their tip?
Answer:
78doalrse
Step-by-step explanation:
solos w
Answer:
$11.40
Step-by-step explanation:
This question asks us to find how much money the family should leave as their tip.
To find the tip, multiply the cost of the total bill by the tip rate.
cost of bill * tip rate
The total bill was $57, and they are leaving a 20% tip
$57 * 20%
Convert 20% to a decimal by dividing by 100 or moving the decimal place 2 spaces to the left.
20/100=0.20
20.0--> 2.0 --> 0.20
20%=0.20
$57 * 0.20
Multiply 57 and 0.20
11.4= $11.40
The family should leave a tip of $11.40
What type of probability is used in this scenario a bag has 10 red marbles 7 blue marbles and 12 yellow marbles the probability of drawing a yellow at random is 12/29
Change2800cm squared into litres
Answer:
You cannot do this because 2800 cm squared is area and liters is volume. however, if you mean 2800 cm cubed, then the answer is 2.8 liters.
Step-by-step explanation:
Pentagon ABCDE is rotated 90° counterclockwise about the origin to form pentagon A'B'C'D'E'. What is the y-coordinate of point C'?
please now
Answer:
The y-coordinate of point C' is 4
Step-by-step explanation:
In the picture attached, pentagon ABCDE is shown.
Rotation 90° counterclockwise about the origin transforms point (x,y) into (-y,x).
C is located at (4, 3), then C' is located at (-3, 4)
Answer:
4
Step-by-step explanation:
2 1 /4 meters by 1 7 /8
[tex](\frac{9}{4} )(\frac{15}{8} )[/tex]
[tex]\frac{135}{32}[/tex]
[tex]=4\frac{7}{32}[/tex]
Find the value of the trig function indicated
Answer:
Step-by-step explanation:
base x height divided by 2
4x3=12
12 divided by 2 = 6
6x5= 30
Consider the curve given by the equation (2y+1)^3 − 24x = −3.
(a) Show that dy/dx = 4/(2y+1)^2.
(b) Write an equation for the line tangent to the curve at the point (−1,−2).
(c) Evaluate d2y/dx2 at the point (−1,−2).
(d) The point (16,0) is on the curve. Find the value of (y−1)′(0).
Answer:
(a) dy/dx = 4/(2y+1)^2.
(b) y = 4/9 x - 14/9
(c) d2y/dx2 = -64/243
Step-by-step explanation:
You have the following equation
[tex](2y+1)^3-24x=-3[/tex] (1)
(a) You first derivative implicitly the equation (1) respect to x:
[tex]\frac{d}{dx}[(2y+1)^3-24x]=\frac{d}{dx}[-3]\\\\3(2y+1)^2(2\frac{dy}{dx})-24=0[/tex]
next, you solve the last result for dy/dx:
[tex]6(2y+1)^2\frac{dy}{dx}=24\\\\\frac{dy}{dx}=\frac{4}{(2y+1)^2}[/tex](2)
(b) The equation for the tangent line is given by:
[tex]y-y_o=m(x-x_o)[/tex] (3)
with yo = -2 and xo = -1
To find the slope m you use the result of the equation (2), because dy/dx evaluated in (-1,-2) is the slope at such point:
m = [tex]\frac{dy}{dx}=\frac{4}{(2(-2)+1)^2}=\frac{4}{9}[/tex]
Hence, by replacing in the equation (3) you obtain:
[tex]y-(-2)=\frac{4}{9}(x-(-1))\\\\y+2=\frac{4}{9}x+\frac{4}{9}\\\\y=\frac{4}{9}x-\frac{14}{9}[/tex]
hence, the equation for the tangent line is y = 4/9 x - 14/9
(c) To find d2y/dx2 you derivative the result obtain in the equation (2):
[tex]\frac{d^2y}{dx^2}=\frac{d}{dx}[4(2y+1)^{-2}]\\\\\frac{d^2y}{dx^2}=-8(2y+1)^{-3}(2\frac{dy}{dx})\\\\\frac{d^2y}{dx^2}=-16(2y+1)^{-3}\frac{dy}{dx}[/tex] (4)
the second derivative for the point (-1,-2) is obtained by replacing y=-2 and dy/dx=m=4/9 in the equation (4):
[tex]\frac{d^2y}{dx^2}=-16(2(-2)+1)^{-3}(\frac{4}{9})=-\frac{64}{243}[/tex]
hence, d2y/dx2 evaluated in (-1,-2) is -64/243
Answer:
(A) The value of [tex]dy/dx=\frac{4}{(2y+1)^2}[/tex].
(B) The equation of the tangent is : [tex]y=(4/9)x-(14/9)[/tex]
(C) The value of [tex]\frac{d^2y}{dx^2}=-64/243[/tex]
(D) The point (16,0) is not on curve so it can not be determined by the given equation.
Step-by-step explanation:
Given information:
The equation [tex](2y+1)^3-24x=-3[/tex]
(A) For the first derivative of the given equation:
[tex]\frac{d}{dx}[(2y+1)^3-24x ]= \frac{d}{dx}(-3)[/tex]
[tex]3(2y+1)^2(dy/dx)-24=0[/tex]
[tex](dy/dx)=\frac{4}{(2y+1)^2}[/tex]
Hence , from the above equation it is shown that the value of
[tex]dy/dx=\frac{4}{(2y+1)^2}[/tex]
(B) The equation of the tangent to the curve is given by:
[tex]y-y_o=m(x-x_0)\\[/tex]
On putting the given values in the above equation
We get:
[tex]m=\frac{4}{(2(-2))+1)^2}[/tex]
[tex]m=4/9[/tex]
Hence, the equation of the tangent can be written as :
[tex]y-(-2)=(4/9)(x-(-1))\\y+2=\frac{4}{9}x+\frac{4}{9}[/tex]
So, the equation of the tangent is :
[tex]y=(4/9)x-(14/9)[/tex]
(C) Now ,
To find [tex]d^2y/dx^2[/tex] for the equation
We have to find double derivative of the equation;
[tex]\frac{d^2y}{dx^2} =\frac{d}{dx}[4(2y+1)^{-2}]\\\frac{d^2y}{dx^2} = -16(2y+1)^{-3}\frac{dy}{dx}[/tex]
On putting the values from the given information in the above equation;
[tex]\frac{d^2y}{dx^2} =-16(2(-2)+1)^{-3}(4/9)[/tex]
[tex]\frac{d^2y}{dx^2}=-64/243[/tex]
(D) For the equation [tex](2y+1)^3-24x=-3[/tex]
First check for the given points (16,0) if it satisfies the given equation or not.
Now on checking for the same the point is not satisfying the given equation hence, we can not find the value of [tex](y-1)'(0)[/tex].
For more information visit:
https://brainly.com/question/5797309?referrer=searchResults
Luke collected 1,034 baseball cards, 1,289 football cards, and 1,566 hockey cards. Use mental math to find the number of cards in Luke’s collection. Solve this problem any way you choose.
Answer:
3889
Step-by-step explanation:
you add all the numbers to get the answer
Answer:3889
Step-by-step explanation:So what u want to do is add them
1034
1289
1566
3889
From a group of 8 people 5 will each win $1000.How many different winning groups are possible?
Answer:
6720 ways different
Step-by-step explanation:
In this case, we must calculate the different ways using the permutation formula:
nPr = n! / (n - r)!
where n is the total number of people and r would come being the group of person that you want to put together the groups, therefore n = 8 and r = 5
replacing:
8P5 = 8! / (8 - 5)!
8P5 = 6720
That is to say that there are 6720 ways different winning groups are possible
Which of the following steps were applied to ABCD to obtain A'B'C'D?
A. shifted 2 units right and 3 units down
B. shifted 3 units right and 2 units down
C. shifted 2 units right and 4 units down
D. shifted 4 units right and 3 units down
Answer:
Option (A)
Step-by-step explanation:
In the figure attached,
Quadrilateral ABCD has been translated to get an image quadrilateral A'B'C'D'.
To get the rule by which the pre-image ABCD has been translated, we will choose a point A(1, 1) from the given pre-image.
Coordinates of point A' are (3, -2).
So the change is,
A(1, 1) → A'(3, -2)
A(1, 1) → A'[(1 + 2), (1 - 3)]
A(x, y) → A'[(x + 2), (y - 3)]
Therefore, point A has been shifted 2 units right and 3 units down.
Option (A) will be the answer.
Find T, N, and kappa for the plane curve Bold r left parenthesis t right parenthesis equalsleft parenthesis 7 Bold cos t plus 7 t Bold font size decreased by 1 sin t right parenthesis Bold i plus left parenthesis 7 Bold sin t minus 7 t Bold font size decreased by 1 cos t right parenthesis Bold j, t greater than 0 .
Find T, N, and for the plane curve r(t) = (7 cost + 7t sin t)i + (7 sin t - 7t cos t)j, t> 0.
Answer:
Step-by-step explanation:
r(t) = (7 cost + 7t sin t)i + (7 sin t - 7t cos t)j
[tex]\frac{d \bar r t}{dt} =(7\frac{d}{dt}\cos t + 7\frac{d}{dt} (t \sin t)i+(7\frac{d}{dt} \sin t-7\frac{d}{dt} t \cos t)j[/tex]
[tex]=(7(-\sin t)+7(1* \sin t+t \cos t))i+(7 \cost -7(1*\cos t - t \sin t))j\\\\=7((-\sin t+\sin t+t \cos t)i+(\cos t-\cos t+t \sin t)j)\\\\=7((t\cos t)i+(t\sin t)j)[/tex]
[tex]\bar r'(t)=\frac{d \bar r t}{dt} =(7t\cos t)i+(7t\sin t)j---(1)\\\\11\bar r(t)=\sqrt{(7t\cos t)^2+(7t\sin t)^2}\\\\=\sqrt{49t^2(\cos^2t+\sin^2 t)} \\\\=7t[/tex]
[tex]\bar T (t)=\frac{\bar r'(t)}{11\bar r(t)11} =\frac{(7t\cos t)i+(7t\sin t)j}{7t} \\\\\barT(t)=(\cos t)i+(\sin t)j[/tex]
[tex]\bar T'(t)=\frac{d}{dt} (\cos t)i+\frac{d}{dt} (\sin t) j\\\\\bar T'(t)=(-\sin t)i+(\cos t)j---(2)\\\\11\bar T'(t)=\sqrt{(-\sin t)^2+(\cos t)^2} \\\\=\sqrt{\sin^2t+\cos^2t} \\\\=1[/tex]
[tex]\bar N(t)=\bar T'(t)=\frac{(-\sin t)i+(\cos t)j}{(1)} \\\\ \large \boxed {\bar N(t)=(-\sin t)i+(\cos t)j}[/tex]
[tex]K(t)=\frac{|\b\r T'(t)|}{\bar r (t)|} \\\\=\frac{|-\sin t i+\cos t j|}{|7t\cos t +7t \sin t j|}[/tex]
Using eq (1) and (2)
[tex]K(t)=\frac{\sqrt{(-\sin t)^2+(\cos t)^2} }{\sqrt{(7t\cos t)^2+(7t\sin t)^2} }\\\\=\frac{\sqrt{\sin^2 t+\cos^2t} }{\sqrt{49t^2(\cos^2 t+\sin^2t)} }\\\\=\frac{\sqrt{1} }{\sqrt{49t^2\times 1} } \\\\ \large \boxed {K(t)=\frac{1}{7t} }[/tex]
What is the solution of StartRoot x minus 4 EndRoot + 5 = 2? x = –17 x = 13 x = 53 no solution
The solution to the given function is determined as 13.
Solution of the function
The solution of the function is calculated as follows;
[tex]\sqrt{x - 4} \ +\ 5 = 2[/tex]
collect similar terms together
[tex]\sqrt{x - 4} \ = 2-5\\\\\sqrt{x - 4} \ = -3[/tex]
square both sides of the equation
[tex](\sqrt{x - 4} )^2 = (-3)^2\\\\x - 4 = 9\\\\x = 9 + 4\\\\x = 13[/tex]
Thus, the solution to the given function is determined as 13.
Learn more about solution of functions here: https://brainly.com/question/10439235
#SPJ9
Answer:
No solution
Step-by-step explanation:
Edge.
Choose the function whose graph is given by:
The function whose graph is given is y = sin (x - 2).
Option B is the correct answer.
What is a function?A function has an input and an output.
A function can be one-to-one or onto one.
It simply indicated the relationships between the input and the output.
Example:
f(x) = 2x + 1
f(1) = 2 + 1 = 3
f(2) = 2 x 2 + 1 = 4 + 1 = 5
The outputs of the functions are 3 and 5
The inputs of the function are 1 and 2.
We have,
The graph of y = sin(x - 2) is a sinusoidal function that is shifted 2 units to the right from the standard sine function y = sin(x).
The sine function oscillates between -1 and 1 as x increases, and the value of x at which the function reaches its minimum or maximum value is a multiple of π.
When we subtract 2 from x in the equation y = sin(x - 2), the entire graph is shifted to the right by 2 units, which means that the minimum and maximum points occur at x-values that are 2 units greater than they would be for the standard sine function.
The graph of y = sin(x - a) is a sinusoidal function that is shifted a units to the right from the standard sine function.
So, in this case, the graph of y = sin(x-2) looks like the standard sine function shifted 2 units to the right.
The amplitude and period of the function remain the same as the standard sine function, but the phase shift changes.
Thus,
The function whose graph is given is y = sin (x - 2).
Learn more about functions here:
https://brainly.com/question/28533782
#SPJ7
Suppose a large shipment of stereos contained 18% defectives. If a sample of size 306 is selected, what is the probability that the sample proportion will differ from the population proportion by less than 6%
Answer:
99.36% probability that the sample proportion will differ from the population proportion by less than 6%
Step-by-step explanation:
To solve this question, we need to understand the normal probability distribution and the central limit theorem.
Normal probability distribution
Problems of normally distributed samples are solved using the z-score formula.
In a set with mean [tex]\mu[/tex] and standard deviation [tex]\sigma[/tex], the zscore of a measure X is given by:
[tex]Z = \frac{X - \mu}{\sigma}[/tex]
The Z-score measures how many standard deviations the measure is from the mean. After finding the Z-score, we look at the z-score table and find the p-value associated with this z-score. This p-value is the probability that the value of the measure is smaller than X, that is, the percentile of X. Subtracting 1 by the pvalue, we get the probability that the value of the measure is greater than X.
Central Limit Theorem
The Central Limit Theorem estabilishes that, for a normally distributed random variable X, with mean [tex]\mu[/tex] and standard deviation [tex]\sigma[/tex], the sampling distribution of the sample means with size n can be approximated to a normal distribution with mean [tex]\mu[/tex] and standard deviation [tex]s = \frac{\sigma}{\sqrt{n}}[/tex].
For a skewed variable, the Central Limit Theorem can also be applied, as long as n is at least 30.
For a sample proportion p in a sample of size n, we have that the sampling distribution of the sample proportions has [tex]\mu = p, s = \sqrt{\frac{p(1-p)}{n}}[/tex].
In this question:
[tex]n = 306, p = 0.18, \mu = 0.18, s = \sqrt{\frac{0.18*0.82}{306}} = 0.0220[/tex].
What is the probability that the sample proportion will differ from the population proportion by less than 6%
This is the pvalue of Z when X = 0.18 + 0.06 = 0.24 subtracted by the pvalue of Z when X = 0.18 - 0.06 = 0.12. So
X = 0.24
[tex]Z = \frac{X - \mu}{\sigma}[/tex]
By the Central Limit Theorem
[tex]Z = \frac{X - \mu}{\sigma}[/tex]
[tex]Z = \frac{0.24 - 0.18}{0.022}[/tex]
[tex]Z = 2.73[/tex]
[tex]Z = 2.73[/tex] has a pvalue of 0.9968
X = 0.12
[tex]Z = \frac{X - \mu}{\sigma}[/tex]
[tex]Z = \frac{0.12 - 0.18}{0.022}[/tex]
[tex]Z = -2.73[/tex]
[tex]Z = -2.73[/tex] has a pvalue of 0.0032
0.9968 - 0.0032 = 0.9936
99.36% probability that the sample proportion will differ from the population proportion by less than 6%
Apply the distributive property to create an equivalent expression.
1/2 (2a−6b+8) = ?
Answer:
a-3b+4
Step-by-step explanation:
1/2 (2a−6b+8) =
=1/2*2a-1/2*6b+1/2*8
=a-3b+4
Answer:
a - 3b + 4
Explanation:
According to the instructions, we must apply the distributive property to create an equivalent expression.
* reminder
distributive property formula: a (b + c) = ab + ac
Let's start by applying the distributive property to the expression.
[tex]\displaystyle\frac{1}{2} (2a - 6b + 8)\\\\\displaystyle\frac{1}{2} (2a) + \displaystyle\frac{1}{2} (-6b) + \displaystyle\frac{1}{2} (8)[/tex]
Simplify by multiplying.
[tex]\displaystyle\frac{1}{2}(2a)+\displaystyle\frac{1}{2}(-6b)+\displaystyle\frac{1}{2}(8)\\\\a+\displaystyle\frac{1}{2}(-6b)+\displaystyle\frac{1}{2}(8)\\\\a-3b+\displaystyle\frac{1}{2}(8)\\\\a-3b + 4[/tex]
Therefore, an equivalent expression to the given expression is a - 3b + 4.
Solve for x in the following 4/2.6=5/x
The value of X is 3.25
Look at the attached picture
Hope it will help you
Good luck on your assignment
What is the value of x?
Answer:
x = 30
Step-by-step explanation:
The exterior angle of a triangle is equal to the sum of the opposite interior angles
100 = 70+x
Subtract 70 from each side
100-70 = 70+x-70
30 =x
Answer:
[tex]x = 30 \: \: degrees[/tex]
Step-by-step explanation:
The sum of the of the exterior angle is equal to sum of the opposite interior angles in a triangle.
[tex]70 + x = 100 \\ x = 100 - 70 \\ x = 30 \: \: \: degrees[/tex]
hope this helps
brainliest appreciated
good luck! have a nice day!
Classify the triangle shown below. Check all that apply.
100°
40°
40°
A. Obtuse
B. Right
C. Isosceles
D. Equilateral
O E. Acute
F. Scalene
Answer:
obtuse
isosceles
Step-by-step explanation:
It has one angle bigger than 90 so it is obtuse
It has two angles that measure the same so it has two sides that measure the same so it is isosceles
The given triangle is an Obtuse triangle.
What is mean by Triangle?A triangle is a three sided polygon, which has three vertices and three angles which has the sum 180 degrees.
We have to given that;
All the angles are,
100°
40°
40°
Here, It has one angle bigger than 90 so it is obtuse.
And, It has two angles that measure the same so it has two sides that measure the same so it is isosceles.
Thus, The given triangle is an Obtuse triangle.
Learn more about the triangle visit;
brainly.com/question/1058720
#SPJ7
Graph a line with a slope of -5 that contains the
point (-3,-4).
y
6
.
.
2
-6
-4
2
4
-6
Answer:
Step-by-step explanation: idk
The highest and lowest scores on a test taken by 80 students are within 19 points of the average of the exam. The average for this exam was a 72. Set up an equation to solve for the highest and lowest scores. Show your original equation and the process used to find the highest and lowest exam score.
1. So start off by asking yourself, how will I get this answer? Absolute values!
2. So what the question is asking is for you to build and equation that shows us how to solve for the highest and lowest grades that are 19 points above and below the average of 72.
3. So your unknown is x, and for us to be able to plug in our highest and lowest scores it will always have to = 19 (that’s the rule we got from the question)
So now this is where your absolute value comes in.
4. Set it up
| x - 72 | = 19
5. Solve it
72-19=53 Minimum
72+19=91 Maximum
6. | 53 - 72 | = 19
| 91 - 72 | = 19
After four years in college, Josie owes $9500 in student loans. The interest rate on the federal loans is 11% and the rate on the private bank loans is 7%. The total interest she owed for one year was $901.00. What is the amount of each loan?
Step-by-step explanation:
federal= $4180
(9500*0.11*4)
private=$2660
(9500*0.07*4)
f f (x) = 5 x minus 25 and g (x) = one-fifth x + 5, which expression could be used to verify g(x) is the inverse of f(x)?
Answer:
We study if the composition of both functions equals the identity ("x"), that is if
[tex]f(g(x))=x[/tex]
Step-by-step explanation:
The composition of the two functions should render 'x" if one is the inverse of the other. That is, we need to find what [tex]f(g(x))[/tex] renders. Notice as well that the same verification could be done with examining [tex]g(f(x))[/tex].
Let's work with [tex]f(g(x))[/tex] :
[tex]f(g(x))=f(\frac{1}{5} x+5)=5\,(\frac{1}{5} x+5)-25= x+25-25=x[/tex]
So we see that the composition of both functions indeed render "x", and that way we have verified that one is the the inverse of the other.
Answer:
B. One-fifth (5 x minus 25) + 5
Step-by-step explanation:
Just got it right on the test.
Point A(3,-2) and point B (-1,6) are endpoints of AB Point C is the midpoint of AB What is the equation of a line perpendicular to that passes through
point c ?
Answer:
y = 0.5x + 1.5
Step-by-step explanation:
I just graphed the points with GeoGebra. Hope this Helps!
Between what two consecutive integers does the square root of 24 lie
4 and 5!
4 squared is 16, which is less than 24, and 5 squared is 25, which is more than 24!
[tex]\sqrt{24}[/tex] lies between two consecutive numbers 4 and 5
Given :
Given square root of 24
Lets write all the perfect square numbers
[tex]\sqrt{4}=2\\\sqrt{9}=3\\\sqrt{16} =4\\\sqrt{25} =5\\\sqrt{36} =6\\\sqrt{49}=7[/tex]
From the above perfect square root numbers, we can see that square root (24) lies between [tex]\sqrt{16} \; and\; \sqrt{25}[/tex]
So we can say that [tex]\sqrt{24}[/tex] lies between 4 and 5
Learn more : brainly.com/question/19028403
What’s the correct answer for this question? Select the ones That apply
Answer:
A and C
Step-by-step explanation:
CD and AB
Answer:
CD & AB
Hope this helps!